Trigeminal Neuralgia, Glossopharyngeal Neuralgia, and Myofascial Pain Dysfunction Syndrome: An Update - Khan, Mohammad; Easmin Nishi, Shamima; Hassan, Siti Nazihahasma; Islam, Md. Asiful; Siew, Hua Gan (Hindawi Publishing Corporation, 2017)
Neuropathic pain is a common phenomenon that affects millions of people worldwide. Maxillofacial structures consist of various tissues that receive frequent stimulation during food digestion.The unique functions (masticatory process and facial expression) of the maxillofacial structure require the exquisite organization of both the peripheral and central nervous systems. Neuralgia is painful paroxysmal disorder of the head-neck region characterized by some commonly shared features such as the unilateral pain, transience and recurrence of attacks, and superficial and shock-like pain at a trigger point.These types of pain can be experienced after nerve injury or as a part of diseases that affect peripheral and central nerve function, or they can be psychological. Since the trigeminal and glossopharyngeal nerves innervate the oral structure, trigeminal and glossopharyngeal neuralgia are the most common syndromes following myofascial pain dysfunction syndrome. Nevertheless, misdiagnoses are common. The aim of this review is to discuss the currently available diagnostic procedures and treatment options for trigeminal neuralgia, glossopharyngeal neuralgia, and myofascial pain dysfunction syndrome.